Gender differences of alexithymia level in students with non-psychotic psychic disorders - Юрценюк, Ольга Сидорівна (Psychiatry, Neurology and Medical Psychology, 2019)
Topicality. Importance of contemporary researches associated with alexithymia at young age is determined by the necessity to change curricula and look for new forms of psychological support directed to social adaptation and harmonious individual development of students.  Objective: to examine alexithymia level in students with non-psychotic psychic disorders depending on gender and diagnosis.  Materials and methods. During 2015-2017 keeping to the principles of bioethics and deontology a comprehensive examination of 1235 students was conducted. The following methods were applied: clinical, clinical-psychopathological, clinical-epidemiological, clinical-anamnestic, experimental-psychological and statistical. The sample had no significant differences in gender and age composition, place of residence, form of study. The survey was conducted in the intersession period. Alexithymic levels were determined using the Toronto Alexithymic Scale (TAS-26) of G. Taylor.Results. The study conducted has given the following results. Primary examination of a general group found a high level of alexithymia in 204 (16,52%) students, after repeated examination this number was 176 (14,52%) (t=0,61). Analysis of a gender aspect of alexithymia in general sampling found that a high level of alexithymia was mostly peculiar for men – 65 (17,81%) as compared with 139 (15,98%) women. Occurrence of a high level of alexithymia was analyzed among the students with non-psychotic psychic disorders. The patients with neurotic disorders associated with stress and somatoform disorders were found to be the most prone to alexithymia manifestation (F 40.0-48.1) – 55,12%. Those with behavioral syndromes associated with physiological disorders and physical factors were found to be least susceptible (F 50.0-51.4) – 7,87%.Conclusions. Considering a considerable value of alexithymia in the formation of non-psychotic psychic disorders screening is recommended to be made in order to find clinically important levels of alexithymia for young people in the course of planned medical check-ups.